The Quick Win: Predictive Accuracy and Structure of Thin Slice Judgments in a Dyadic Negotiation. - Todgham, Mary Anne. (2017)
Abstract: Accurate first impression judgments require surprisingly little information, such as a 30-second video clip or even a photograph (Ambady & Rosenthal, 1993; Rule & Ambady, 2008). Most of this research has measured accuracy by comparing judgments to self- or other-ratings, though recent work has found that first impressions also accurately predict real-world outcomes (e.g. Rule & Ambady, 2008). In this dissertation, I extend research on the objective accuracy of first impression judgments by examining the accuracy of judgments of based on thin slices of nonverbal behavior of a dyadic negotiation with a measurable outcome. In the first set of studies, participants viewed 20-second silent clips of a videotaped role-played negotiation and judged "likelihood of winning", self-profitable traits, and other-profitable traits. "Likelihood of winning" and the self-profitable trait composites (Dominance, Intelligence, Social Problem-Solving Skills) predicted outcomes for high-power negotiators, while only the Dominance composite predicted outcomes for low-power negotiators. The other-profitable trait composite (Warmth) did not predict outcomes for either role. An investigation of the indirect effects of first impressions on outcomes found that offer tactics (sequential versus simultaneous offers) mediate effects between displays of Intelligence and Social Problem-Solving Skills and outcomes. In the second set of studies, I examined the variance component structure of thin slice judgments using generalizability theory (Cronbach, Gleser, Nanda, & Rajaratnam, 1972). Specifically, these analyses measured the degree to which different perceivers, different channels (face, verbal content, and tone of voice), different instances over time (first impression, second impression, and third impression), and different roles (high-power versus low-power) contribute to the variability of dominance, likeability, and competence judgments. Differences discovered in temporal stability and consensus based on channel and role have implications for future social judgment research. Integration of the structural and analytical approaches, offers some new hypotheses on the impact of time, channel, and target role on behavior and social perception.; Thesis (Ph.D.)--Tufts University, 2013.; Submitted to the Dept. of Psychology.; Advisor: Nalini Ambady.; Committee: Keith Maddox, Sam Sommers, and Nicolas Rule.; Keyword: Social psychology.